The Combined Effect of Leaflet and Demonstration Media on the Knowledge of Pregnant Women with Chronic Energy Deficiency in Coastal and Mining Areas of Kolaka Regency - Astim Astim; Tasnim; Wa Ode Nova Noviyanti Rachman (Magister Kesehatan Universitas Mandala Waluya, 2026)
Introduction: Chronic Energy Deficiency is a health problem for pregnant women which is a condition of imbalance in nutritional intake between energy and protein. The prevalence of Chronic Energy Deficiency in the coastal area of ​​Wolo Health Center in 2023 was 11.7% and in the mining area of ​​Iwoimendaa Health Center was 16.8%. The purpose of this study was to determine the Combined Effect of Leaflet and Demonstration Media on the Knowledge of Pregnant Women with Chronic Energy Deficiency in Coastal and Mining Areas of Kolaka Regency. Method: This research is quantitative, with a pre-experimental design (one group pre-test post-test design). The population was all pregnant women with chronic energy deficiency in the coastal and mining areas of Kolaka Regency, totaling 67 people, and a sample of 40 people obtained using proportional random sampling techniques. Data were collected using questionnaires with leaflets and demonstration methods. Result: The Mc.Neymar test on leaflet provision on knowledge obtained a p value of 0.002, attitude p value of 0.016 and eating patterns p value of 0.031. Then the combined provision of leaflets and demonstrations obtained a p value of 0.000, attitude p value of 0.31 and eating patterns p value of 0.002. Conclusion: There is an influence of leaflet media on the knowledge, attitudes, and dietary patterns of pregnant women with Chronic Energy Deficiency, then there is an influence of combined media of leaflets and leaflet demonstrations on knowledge.